Reaction of Epoxides. V. 1, 3-Dipolar Cycloaddition Reaction of Epoxides with Carbon-Nitrogen Double Bond Compounds - KOJIMA, YOKO; FURUKAWA, MITSURU; SUGITA, MAKOTO; HAYASHI, SEIGORO (Chemical & pharmaceutical bulletin, 1974)
The reaction of epoxides with several conjugated C-N double bond compounds was attempted. Aromatic aldazines were found to undergo criss-cross cycloaddition toward epoxides. On the other hand, aromatic ketazines gave the oxazolidines formed by the cycloaddition of one molecule of epoxides to one of the C-N double bond of the ketazines. Moreover, in the reaction with N, N'-bis-benzylidene-p-phenylenediamine and N, N'-p-phenylene-bis-methylidenaniline, cycloaddition of two molecules of epoxides to two C-N double bonds of these compounds occurred to give the corresponding p-phenylenebis-oxazolidines.